Efficacy and Safety of Sofosbuvir‐Based Antiviral Therapy to Treat Hepatitis C Virus Infection After Kidney Transplantation. Issue 5 (20th November 2015) - Kamar, N.; Marion, O.; Rostaing, L.; Cointault, O.; Ribes, D.; Lavayssière, L.; Esposito, L.; Del Bello, A.; Métivier, S.; Barange, K.; Izopet, J.; Alric, L.
Abstract: There is no approved therapy for hepatitis C virus (HCV) infection after kidney transplantation, and no data regarding the use of new‐generation direct antiviral agents (DAAs) have been published so far. The aims of this pilot study were to assess the efficacy and safety of an interferon‐free sofosbuvir‐based regimen to treat chronic HCV infection in kidney transplant recipients. Twenty‐five kidney transplant recipients with chronic HCV infection were given, for 12 (n = 19) or 24 weeks (n = 6), sofosbuvir plus ribavirin (n = 3); sofosbuvir plus daclatasvir (n = 4); sofosbuvir plus simeprevir, with (n = 1) or without ribavirin (n = 6); sofosbuvir plus ledipasvir, with (n = 1) or without ribavirin (n = 9); and sofosbuvir plus pegylated‐interferon plus ribavirin (n = 1). A rapid virological response, defined by undetectable viremia at week 4 after starting DAA therapy, was observed in 22 of the 25 patients (88%). At the end of therapy, HCV RNA was undetectable in all patients. At 4 and 12 weeks after completing DAA therapy, all had a sustained virological response. The tolerance to anti‐HCV therapy was excellent and no adverse event was observed. A significant decrease in calcineurin inhibitor levels was observed after HCV clearance. New‐generation oral DAAs are efficient and safe to treat HCV infection after kidney transplantation. Abstract : In 25 hepatitis C–positive kidney transplant patients treated with direct‐acting antiviral drugs, the authors report a sustained virological response at 12 weeks in all patients with no significant adverse events. See also the brief communication from Sawinski et al (page 1588 ) and the editorial from Saxena and Terrault (page 1345 ).